Water Migration and Segregated Ice Formation in Frozen Ground: Current Advances and Future Perspectives - Fu, Ziteng; Wu, Qingbai; Zhang, Wenxin; He, Hailong; Wang, Luyang (Frontiers in Earth Science, 2022)
A characteristic of frozen ground is a tendency to form banded sequences of particle-free ice lenses separated by layers of ice-infiltrated soil, which produce frost heave. In permafrost, the deformation of the ground surface caused by segregated ice harms engineering facilities and has considerable influences on regional hydrology, ecology, and climate changes. For attention to predicting the engineering and environmental impacts of permafrost degradation and segregated ice transformation under a warming climate, establishing appropriate mathematical models to describe water migration and ice behaviour in frozen soil is necessary. This requires an essential understanding of water migration and segregated ice formation in frozen ground. This article reviews mechanisms of water migration and ice formation in frozen soils and their model construction and introduce the effects of segregated ice on the permafrost environment included landforms, regional hydrological patterns, and ecosystems. Currently, the soil water potential has been widely accepted to characterize the energy state of liquid water, to further study the direction and water flux during water moisture migration. Models aimed to describe the dynamics of ice formation have successfully predicted the macroscopic processes of segregated ice, such as the rigid ice model and segregation potential model, which has been widely used and further developed. However, some difficulties still need further study to describe their theoretical basis of microscope physics. Besides, how to describe the ice lens in the landscape models is another interesting challenge that helps to understand the interaction between soil ice segregation and the permafrost environment. In the final of this review, we outline some concerns that current research has overlooked, which should be the central focus in future research.